Caries Status and Associated Factors in Children with Intellectual Disabilities: A Systematic Review and Meta-Analysis - Ningrum, Valendriyani; Bakar, Abu (Scripta Medica, 2025)
Children with intellectual disabilities (IDs) have incapacitated on day life activities, chewing or swallowing problems, drooling saliva and other factors influence poor oral hygiene. The study aimed to explore scientific literatures related caries status and factor associated in children with IDs. This comparative study was a systematic review and meta-analysis regarding the caries status between children with IDs and control group. The study was conducted on five data bases: PubMed, Web of Science, Scopus, Wiley Online and Cochrane Library published from January 2004 to 15 January 2020. The reliability of the selection of the papers was very high (Kappa = 0.91). Review Manager (RevMan 5.3.3) was used for meta-analysis with p-value < 0.05. The initial search yielded 2337 articles. Twenty-four studies included in qualitative synthesis demonstrated several factors affected caries in IDs children consisted of parental awareness, severity of disorder, dietary intake, oral biology factor, medication use, dental professional acceptance and financial barrier. Thirteen studies included in quantitative synthesis showed the caries in children with intellectual disability was higher than normal children (p < 0.001). Children with IDs showed higher caries rates than general children. The findings suggest children with IDs support are necessary from their parents/caregivers, dental professional and policy maker to improve oral health promotion and prevention.
Keywords: Dental caries; Intellectual disability; Child